Implementation of Analytical Hierarchy Process Method in Selecting Active Lime Suppliers at PT Aneka Jasa Grhadika: Terapan Metode Analytical Hierarchy Process Pada Pemilihan Supplier Kapur Aktif di PT Aneka Jasa Grhadika - Mutiara Rahmi; Tranggono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
In a competitive business world, supplier selection is a strategic element to ensure the sustainability of a company's operations. PT Aneka Jasa Grhadika, which operates in the construction industry sector, requires high-quality raw materials such as quicklime to support the success of its projects. This study applies the Analytical Hierarchy Process method to supplier selection to provide recommendations for determining the best quicklime supplier for PT Aneka Jasa Grhadika. The Analytical Hierarchy Process method is a multi-criteria decision-making method that combines quantitative and qualitative approaches to compile a hierarchy of problems and assess alternative solutions based on predetermined criteria weights. Supplier evaluation is carried out based on strategic criteria that include cost, quality, service, safety, and occupational health. Data is obtained through interviews and direct observations in the field, then processed to produce priorities in decision making. The results of the analysis show that this method can be used effectively as a systematic approach in supply chain management in the construction sector. For company partners, it is recommended to routinely evaluate supplier performance by considering changes in operational needs and market dynamics, in order to ensure supply sustainability and increase operational efficiency.